MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATERI SISTEM KOLOID DENGAN MENGGUNAKAN MODEL PEMBELAJARAN ARIAS BER-SETTING MODEL KOOPERATIF TIPE JIGSAW - Siti Arafah; Abdul Hamid (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2016)
Abstrak: Has conducted research that aims to determine the increase (1) the activities of teachers, (2) the activity of students, (3) the results of student learning (4) the student's motivation and (5) student response to learning with learning model ARIAS air-setting model of cooperative jigsaw the material colloidal system. The study design was a classroom action research (CAR) with two cycles. Each cycle consists of planning, action, observation and evaluation, as well as analysis and reflection. The subjects were students of class XI SMA Muhammadiyah 1 Banjarmasin with the number of 20 people. File were collected through observation, achievement test and questionnaire. File were analyzed by using descriptive analysis of quantitative and qualitative analysis. The results showed that learning with learning model ARIAS Ber-setting type of jigsaw cooperative model can enhance the activity of teachers in the implementation of the action with a 44.33 score enough category in the first cycle to 63.7 with excellent category on the second cycle. Activities of students in the first cycle increased from a score of 44.5 with enough categories to 62 categories very well in the second cycle. The motivation of students increased by 30% in both categories. Percentage of cognitive learning outcomes of students in the classical style in the first cycle of 40% increase in the second cycle to 100% and affective learning outcomes of students in the first cycle by 76 in the medium category increased to 90 in very high. Students respond positively to the learning model ARIAS Ber-setting model of cooperative jigsaw.Keywords: learning outcome, motivation, ARIAS, Jigsaw, colloid